2000
DOI: 10.1590/s0104-79302000000100002
|View full text |Cite
|
Sign up to set email alerts
|

The scorpion envenoming syndrome: a different perspective. The physiological basis of the role of insulin in scorpion envenoming

Abstract: Death caused by scorpion envenoming (Buthidae family) is a common event in tropical and subtropical countries. Severe scorpion envenoming causes an autonomic storm resulting in a massive release of catecholamines, angiotensin II, glucagon, cortisol, and changes in insulin secretion. As a consequence of these changes in the hormonal milieu, scorpion envenoming results in a syndrome of fuel energy deficits and an inability of the vital organs to utilize the existing metabolic substrates, which causes myocardial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 57 publications
2
32
0
Order By: Relevance
“…Many studies have emphasized that blood glucose levels increase after envenomation resulting in hyperglycemia in animal models (10,16,22,(27)(28)(29)(30)(31)49) and patients (2,11,12,47). In the present study, hyperglycemia was seen after A. crassicauda venom administration.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Many studies have emphasized that blood glucose levels increase after envenomation resulting in hyperglycemia in animal models (10,16,22,(27)(28)(29)(30)(31)49) and patients (2,11,12,47). In the present study, hyperglycemia was seen after A. crassicauda venom administration.…”
Section: Discussionsupporting
confidence: 55%
“…In the present study, hyperglycemia was seen after A. crassicauda venom administration. Several studies have reported that this might be due to a massive release of catecholamines, increased glucagon and cortisol levels, changes in thyroid hormone levels, and changes in insulin secretion (20,(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin has been used to reverse the pathophysiology of envenomation [14]. It has been explained on the basis of insulin resistance resulting from autonomic storm and massive release of free fatty acids [14].…”
mentioning
confidence: 99%
“…It has been explained on the basis of insulin resistance resulting from autonomic storm and massive release of free fatty acids [14]. In addition, increased levels of TNFα and other inflammatory cytokines (IL 1β and IL 6) also produce insulin resistance [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation